One-Dimensional and Multi-Dimensional Studies of the Exocentric Distance Estimates in Frontoparallel Plane, Virtual Space, and Outdoor Open Field - Aznar Casanova, J. Antonio; Matsushima, Elton H.; Ribeiro Filho, Nilton P.; Da Silva, José A. (The Spanish Journal of Psychology, 2006)
Sin resumen